INTEGRATING NATIONAL AND GLOBAL ART THROUGH CULTURAL CONNECTIONS: CHALLENGES AND APPROACHES - Qurbonova Sitora Yunus qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article examines how material diversity in sculpture lessons can enhance the quality and effectiveness of practical activities. The study highlights the pedagogical benefits of using various materials, including traditional ones such as clay, gypsum, and wood, as well as modern materials like polymer and plastic. By integrating multiple materials, students develop technical skills, creativity, and artistic problem-solving abilities. This approach fosters active engagement, practical competence, and imaginative thinking, ultimately improving the overall learning outcomes in sculpture education.